Making Sense of Noise – A Symphony for Voices - McLaren, Mary-Rose (Imaginations)

(untitled) (York University, 2021)
This paper uses original and found poetry to shape the soundscape of 2020 into meaning. A critical auto-ethnographic study, it uses poetic strategies of arts-based methodology to weave stories, experiences and impressions together, to create a literary fabric of the year. So doing, it creates a choral piece for the spoken voice, which explores ideas of conspiracy, community, racism, oppression and justice, drawing on the author’s experience in Australia, and connection with the wider world via the internet. Its focus on listening as meaning is formed from competing and contesting voices.